The Divergence between Self- and Preceptor-Assessments of Student Performance during Advanced Pharmacy Practice Experiences - Tonya Brim-Dauterman; Shantanu Rao (MDPI AG, 2024)
(1) Objectives: A divergence in self- and preceptor-evaluations of clinical skills has been noted during Advanced Pharmacy Practice Experiences (APPEs). The goal of this study was to determine the domains of overestimation of clinical skills by students during their APPE rotations. (2) Methods: Preceptor-assigned grades for APPE rotations from 2017-2022 were analyzed to identify instances of letter grade B or lower. The self- and preceptor-evaluations of APPE rotation were compared to determine the domains of divergence in evaluation between students and preceptors. (3) Results: Between 2017 and 2022, 305 student APPE rotations were graded as B or lower (~14%) by the preceptors. A statistically significant difference was noted between self- and preceptor-assigned letter grades across all practice settings including ambulatory patient care, community pharmacy, general medicine patient care, hospital/health system pharmacy, and special population patient care APPE rotations. In addition, examining the self- and preceptor evaluation rubric for these rotations revealed a statistically significant overestimation of clinical skills by students in all 9 domains of APPE evaluation. Finally, the divergence in the rating of clinical skills between student- and preceptor evaluation was found to be highest in the domains of planning and follow-up of patient care, disease knowledge, and communication with patients. (4) Conclusions: Students who fail to exhibit exemplary practice readiness during APPEs tend to overestimate their clinical skills in all domains of APPE evaluation. The results from our study support the need for additional avenues to assist in the identification of deficits in student learning before APPEs to increase their self-awareness (metacognition).